Trace Elements in Condiments Commonly Used in Pakistan - Khan, M.R.; Rashid, C.M. (Asian Journal of Chemistry, 2012)
Trace elements such as iron, cobalt, copper, manganese and nickel were determined in condiments popularly used and available in Pakistan, by atomic absorption spectrometry. The results indicated that spices such as caraway, parsley and cumin were rich in all the trace metals. Turmeric, onion seeds and dried ginger contained quite an appreciable amount of trace metals. The amount of iron was usually high in nearly all the spices. Caraway and onions were particularly rich source of this metal. Parsley, cumin and ginger contained moderate amount of iron, while ginger, cardamom and cinnamon were rich in manganese as these contained more than 100 μg/g of metal. Garlic contained less than 10 μg/g nickel and copper contents were very low in all the spices. These were usually in the range of 1-2 μg/g.